THE ROLE ANALYSIS OF INDONESIA'S POLICY STRATEGY ON INDO-PACIFIC - Aisyah Dwi (Journal of Diplomacy and International Studies, 2020)
The emergence of Indo-Pacific terminology which is increasingly developing causes the interest of countries to be involved in the role of the region increasingly high for various reasons. Indonesia as an archipelagic country has the opportunity to improve its strategic position to support of the "Indo-Pacific" concept. Therefore, this article tries to analyze the role of Indonesia's policy strategy towards the Indo-Pacific. In this article, the author wants to analyze and provide an overview of the role of Indonesian policy in the Indo-Pacific region. This research is a descriptive study with a qualitative approach. Based on policy analysis, the results found, Indonesia has a role as a middle power in the Indo-Pacific region. Indonesia as an archipelago utilizes the strategic role of its region by implementing maritime policy to become the world's maritime axis in the Indo-Pacific region. Indonesia made ASEAN the centrality of its policies in promoting the Indo-Pacific. The Implementation and Movement of Policies undertaken by Indonesia towards the Indo-Pacific are in accordance with the perspective and national interests of the country which take advantage of opportunities and maximize profits in the geographical structure of the region.